2021
DOI: 10.1503/cjs.003419
|View full text |Cite
|
Sign up to set email alerts
|

Wait times, resource use and health-related quality of life across the continuum of care for patients referred for total knee replacement surgery

Abstract: Background: The escalating socioeconomic burden of knee osteoarthritis (OA) underscores the need for innovative strategies to reduce wait times for total knee arthroplasty (TKA). The purpose of this study was to evaluate resource use, costs and health-related quality of life (HRQoL) across the continuum of care for patients with knee OA. Methods: This was a prospective study of 383 patients recruited from a high-volume teaching hospital at different stages of care (referral, consultation and presurgery). Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Eighteen studies were identified as eligible for this systematic review (Aoyagi et al., 2021; Bedard et al., 2017; Cronström et al., 2020; Dhawan et al., 2014; Grace et al., 2022; Hofstede et al., 2015; Ingelsrud et al., 2020; Jacobs et al., 2022; King et al., 2020; Lamb et al., 2008; Lange et al., 2018; Lebedeva et al., 2021; McHugh et al., 2007, 2011; Power et al., 2005; van Zaanen et al., 2020; Ward, 2021; Warwick et al., 2020) (see flowchart in Figure 1). After screening 1306 titles/abstracts and 36 full‐text articles, 12 studies were identified through the literature search (Bedard et al., 2017; Dhawan et al., 2014; Grace et al., 2022; Ingelsrud et al., 2020; Jacobs et al., 2022; King et al., 2020; Lamb et al., 2008; Lange et al., 2018; Lebedeva et al., 2021; McHugh et al., 2007; van Zaanen et al., 2020; Ward, 2021), whereas six additional studies were found through reference checking of the included studies (Aoyagi et al., 2021; Cronström et al., 2020; Hofstede et al., 2015; McHugh et al., 2011; Power et al., 2005; Warwick et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen studies were identified as eligible for this systematic review (Aoyagi et al., 2021; Bedard et al., 2017; Cronström et al., 2020; Dhawan et al., 2014; Grace et al., 2022; Hofstede et al., 2015; Ingelsrud et al., 2020; Jacobs et al., 2022; King et al., 2020; Lamb et al., 2008; Lange et al., 2018; Lebedeva et al., 2021; McHugh et al., 2007, 2011; Power et al., 2005; van Zaanen et al., 2020; Ward, 2021; Warwick et al., 2020) (see flowchart in Figure 1). After screening 1306 titles/abstracts and 36 full‐text articles, 12 studies were identified through the literature search (Bedard et al., 2017; Dhawan et al., 2014; Grace et al., 2022; Ingelsrud et al., 2020; Jacobs et al., 2022; King et al., 2020; Lamb et al., 2008; Lange et al., 2018; Lebedeva et al., 2021; McHugh et al., 2007; van Zaanen et al., 2020; Ward, 2021), whereas six additional studies were found through reference checking of the included studies (Aoyagi et al., 2021; Cronström et al., 2020; Hofstede et al., 2015; McHugh et al., 2011; Power et al., 2005; Warwick et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen of the included studies used a cross‐sectional study design (Aoyagi et al., 2021; Bedard et al., 2017; Cronström et al., 2020; Dhawan et al., 2014; Grace et al., 2022; Hofstede et al., 2015; Ingelsrud et al., 2020; Jacobs et al., 2022; King et al., 2020; Lange et al., 2018; Power et al., 2005; van Zaanen et al., 2020; Ward, 2021; Warwick et al., 2020), three studies used a longitudinal study design (prospective) (Lebedeva et al., 2021; McHugh et al., 2007, 2011), and one study used a non‐randomised interventional design without a control group (Lamb et al., 2008). Response rate was considered ‘not applicable’ for six studies, because data were extracted from data‐bases and medical records (Aoyagi et al., 2021; Bedard et al., 2017; Dhawan et al., 2014; Lange et al., 2018; Ward, 2021; Warwick et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Any other effects of waiting time on health status and QALY gains were not included in our analysis, as conflicting evidence had been found in the literature. Various studies did not find a clear effect of waiting time on postoperative health status ( Ostendorf et al, 2004 ; Tuominen et al, 2010), while others found that waiting time was associated with a poorer health after surgery (worse in – worse out) ( Clement et al, 2021 ; Lebedeva et al, 2021 ; Röder et al, 2007 ; Vergara et al, 2011 ). T is likely that the prolonged waiting times during the pandemic have led to additional health losses, for example due to disease progression or premature death.…”
Section: Strengths and Limitationsmentioning
confidence: 99%